Impact of weather systems on observed precipitation at Ny-Ålesund (Svalbard) - K. Ebell; C. Buhren; R. Gierens; G. Chellini; G. Chellini; M. Lauer; M. Lauer; A. Walbröl; S. Dahlke; P. Krobot; M. Mech (Atmospheric Chemistry and Physics)
Ground-based precipitation observations are sparse in the Arctic but are needed to better understand precipitation processes and to provide reference data sets for models and satellite products. This study presents new, temporally highly resolved precipitation measurements from a Pluvio precipitation gauge and a Parsivel disdrometer at the Arctic research station AWIPEV, part of the Ny-Ålesund Research Station, Svalbard. Using the information on the precipitation phase by Parsivel, we derived a temperature-dependent separation of precipitation into liquid and solid mass. The Pluvio precipitation amount and the Parsivel/temperature-based precipitation type were analyzed for the period August 2017–December 2021 and related to the presence of synoptic-scale weather systems, i.e., atmospheric rivers (ARs), cyclones and fronts, detected from ERA5 reanalysis data. ARs occurred only 8 % of the time at Ny-Ålesund but contributed to about 42 % of the total precipitation amount with a high liquid mass fraction (72 %). Cyclones occurred 20 % of the time and were associated with 39 % of the precipitation, mainly in solid form (62 %). Frontal systems play a minor role in the precipitation amount at Ny-Ålesund. Extreme events, i.e., days with daily precipitation sums above the 98th percentile, contribute 18 % to the total precipitation amount. All of these events are related to enhanced water vapor transport, often in the form of ARs and in combination with fronts and a high liquid mass fraction. Liquid precipitation in winter is mainly connected to ARs. These new measurements will help to better characterize uncertainties in gauge-based precipitation observations and the local variability of precipitation.